Aves de la ladera oriental de los andes orientales, alto río cusiana, boyacá, colombia (1971)
The bird collection (52 species and subspecies) treated in this paper was collected in the upper Cusiana River, eastern slope of the Eastern Andes, Departamento de Boyacá, Colombia. In the introduction are given geographical details of the proper area where the material was secured.  This study is very important because of the little knowledge on the ornisof the Eastern Andes in Boyacá. Some light is thrown on the similarities and discrepancies between the avifaunas of Boyacá and Cundinamarca (Eastern Andes) and also on the relations with the adjacent regions of Venezuela.  The intergradation of Atlapetes semirufus zimmeri with A. s. semirufus is discussed and the subspecies Hemispingus frontalis flavidorsalis isadded to the colombian avifauna. Previous local avifaunas of the Andes in Boyacá are: Borrero and Olivares (1955) and Olivares (1963).